Psychological features of motivation for altruistic behavior of an individual in the context of transactional analysis - TRAVERSE, Tetiana; KOLUPAIEV, Borys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Altruistic behavior in adults during wartime has been studied. Modern research across various methodological approaches has been analyzed, examining the content and structure of altruism as a psychological phenomenon. The aim of this study is to reveal the content and structure of the psychological features of motivation for altruistic behavior in adults.Methods. Methods of analyzing contemporary psychological literature on personality behavior motivation and transactional analysis have been employed. Additionally, theoretical and empirical methods, psychodiagnostic techniques, and mathematical-statistical data processing methods have been utilized.Results. It has been determined that behavioral patterns associated with internal drivers influence an individual's inclination toward altruism. The content and structure of these drivers in the motivation of altruistic behavior have been found to shape its manifestations and connections with generative altruism.It has been revealed that in early adulthood, positive correlations are observed between behavioral altruism, the dominant driver "Be Strong," and generative altruism. In middle adulthood, a moderate positive correlation has been identified between behavioral altruism and the "Try Hard" driver, indicating a stronger orientation toward behavioral rather than generative altruism.It has been established that personal values significantly impact the manifestation of altruism. It has been suggested that drivers related to striving for high standards, self-actualization, and self-control may stimulate both behavioral and generative altruism.Conclusions. It has been argued that individuals oriented toward self-realization and self-actualization are more likely to display altruistic behavior that aligns with their internal beliefs, life goals, and social expectations. Such an altruistic orientation may also be motivated by the need to confirm one's resilience and responsibility toward others, as well as by the expectation of reciprocal behavior from others. Individual strategies for each driver have been identified to ensure a harmonious balance between helping others and self-care.
Keywords: altruistic behavior; drivers; personality motivation; altruistic orientation; self-realization and self-control; helping others; life goals